A history of American poetry - Gray, Richard 1944- (John Wiley & Sons, Ltd, 2015)
A History of American Poetry presents a comprehensive exploration of the development of American poetic traditions from their pre-Columbian origins to the present day. Richard Gray, one of the leading authorities on American literature, situates the story of American poetry within the historical, political, cultural, and societal contexts that contributed to shapingw the genre. Through close readings of individual poems, Gray reveals how American poetry evolved to reflect the rich diversity and multicultural character of the United States. While the primary focus is on poetry of the twentieth and twenty-first centuries, numerous formative and influential figures from the colonial and revolutionary eras through the nineteenth century are not overlooked, with coverage of voices ranging from Edward Taylor, Anne Bradstreet, and Phillis Wheatley to Poe, Whitman, and Dickinson. Presenting the full breadth of American poetry in an accessible and engagingly written manner, A History of American Poetry is an invaluable guide to all facets of this essential component of the nation's rich literary heritage--Book jacket.